الإلتزام بالمسؤولية الإجتماعية في المؤسسة من أجل تحقيق التنمية المستدامة -دراسة حالة مؤسسة فولفو- - نبيلة جلابي; إناس ذوايبية (My University, 2021)
The present study aimed at elucidating the approach adopted by Volvo towards arriving at efficient solutions to handle the task of reconciling between economic, environmental, and social considerations so as sustainable development is secured. To this end, the concept of social accountability is held cardinal. The extant account deploys into service the descriptive method whereby the study results foreground Volvo Group’s potential for refining their services in alignment with economic, social, and environmental regards, altogether. The study culminates in offering insight as to the imperativeness of exercising social accountability not solely as a modus for an establishment’s to maintain public respect, but as one that forms a holistic procedure mediating a an approach mindful of environmental, economic, and social exigencies, seeking, ultimately, the realisation of a sophisticated sustainable development philosophy. ............................................... هدفت الدراسة إلى بيان التوجه الذي تبنته مؤسسة فولفو في سعيها بلوصول لحلول ناجعة لمعالجة اشكالية التوفيق بين الجوانب الاقتصادية والبيئية والاجتماعية لتحقيق التنمية المستدامة وذلك من خلال تبني مفهوم المسؤولية الاجتماعية، حيث تم استخدام المنهج الوصفي التحليلي لتحقيق ذلك، وكانت أهم نتائج الدراسة هي مقدرة مجموعة فولفو على التحسين كل من الجوانب الاقتصادية والاجتماعية والبيئية معا، مما يدفع بضرورة الاعتقاد بأن تبني المسؤولية الاجتماعية وتطبيقها ليس مجرد عملية أو نشاط تسعى من خلاله المؤسسة لبناء صورة جيدة عنها، بل هو عملية تكاملية بين التفكير البيئي والتفكير الاقتصادي والتفكير الاجتماعي بمعنى اخر هو فلسفة لتجسيد التنمية المستدامة.